A study of the effects of light, sound, and bubble curtains on the expulsion effect of Hexagrammos otakii - Dai, Li; Zhang, Zhen; Liu, Jinhu; Chen, Jianxin; Zhang, Yu; Zhang, Wenjie; Li, Qi; Bai, Wei; Zhang, Rongyong; Xiao, Hao (Frontiers in Marine Science, 2024)
To investigate the expulsion effect of different expulsion modes on Hexagrammos otakii, this study examined various environmental conditions in an indoor tank. Specifically, different lighting conditions (white, blue, and green light at illumination intensities of 5000 lx, 8000 lx, and 10000 lx) were explored, as well as varied sound conditions (sound frequencies of 150 Hz, 300 Hz, and 450 Hz at different sound pressure levels of 130 dB, 140 dB, and 150 dB) and bubble curtain conditions (air volumes of 60 L/min, 120 L/min, and 180 L/min). Additionally, the expulsion effect of different fish densities (1.56 tails/m2, 2.35 tails/m2, 3.13 tails/m2) of Hexagrammos otakii was investigated. The findings revealed that the bubble curtain exhibited the most effective expulsion effect on Hexagrammos otakii, with an expulsion rate of (40.4 ± 12.0) %, the highest period of 53%, and an average expulsion distance of 3.0 expulsion intervals when the air volume was 180 L/min and the fish density was 1.56 tails/m2. Conversely, the expulsion effect of light and sound on Hexagrammos otakii was found to be insignificant, with the expulsion rate of sound not exceeding 20% and that of light being lower than 15%. These results have implications for the selection and design of fish expulsion equipment in offshore areas, such as those surrounding wind farms and nuclear power plants. Therefore, this study provides valuable scientific reference for resource managers and practitioners in the field.